An Overview of Ecological Deterioration in the “The City of Saints”–Hoshiarpur (Punjab, India) - Dhami, Kirandeep K. (Novel Perspectives of Geography, Environment and Earth Sciences Vol. 8, 2023)
Hoshiarpur is a small town in the northern state of Punjab in India that remained ecologically rich until recently, when unplanned urbanization, population explosion and humungous tree cutting contributed in large to a disturbed ecology within the city. For being situated at the foothills of Shivalik ranges, the city was known for its ecological beauty almost fifty years back. It was viewed mostly green with large seasonal drains overflowing with rainy waters during monsoon season while the air was clean enough to bring the visibility of shivalik ranges at the back of the drains. In the foothills of shivalik range with river like waters overflowing amidst the green cover, it is remembered as one of the most beautiful towns in the state of Punjab (India). The current state of ecology in the city is very gloomy. The city was ranked as one of the dirtiest in a nationwide survey conducted by Urban Development Ministry in 2015. The city hasn’t seen any improvement since then despite its lowest ranking. This work is a small effort to provide a broader overview of massive ecological degradation that has taken place in the city over the past fifty years and suggest the path towards its ecological restoration and remediation.